Living and Dying with Hard Pegs : The Rise and Fall of Argentina's Currency Board - De la Torre, Augusto; Levy Yeyati, Eduardo; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
The rise and fall of Argentina's currency board shows the extent to which the advantages of hard pegs have been overstated. The currency board did provide nominal stability and boosted financial intermediation, at the cost of endogenous financial dollarization, but did not foster monetary or fiscal discipline. The failure to adequately address the currency-growth-debt trap into which Argentina fell at the end of the 1990s precipitated a run on the currency and the banks, followed by the abandonment of the currency board and a sovereign debt default. The crisis can be best interpreted as a bad outcome of a high-stakes strategy to overcome a weak currency problem. To increase the credibility of the hard peg, the government raised its exit costs, which deepened the crisis once exit could no longer be avoided. But some alternative exit strategies would have been less destructive than the one adopted.